Patterns of Psychiatric Illness over 3 years: A single Centre Inpatient Study From Nepal - Dhungana, S; Chapagai, M; Tulachan, P; Ojha, S P (Journal of Psychiatrists' Association of Nepal, 2015)
Introduction: Inpatient psychiatric patients are a major group of our treatment domain and they are different from outpatients in certain characteristics. In this study, we assessed the patterns of psychiatric illnesses along with socio-demographic variables in patients admitted in a psychiatry ward of a tertiary hospital over three consecutive years.Methods: This is a retrospective review of all patients admitted in psychiatry ward Tribhuvan University Teaching Hospital over a three year period between 2067 Baisakh to 2069 Chaitra (2010 April to 2013 April) by reviewing in-patient admission charts from medical records section of the hospital. Descriptive analysis was done by using SPSS version 19; Chicago, IL, with p value of